2010
DOI: 10.3171/2009.11.spine09172
|View full text |Cite
|
Sign up to set email alerts
|

Posterior occipitocervical (C0–3) fusion using polyaxial occipital condyle to cervical spine screw and rod fixation: a radiographic and cadaveric analysis

Abstract: Numerous conditions affect the occipitocervical junction requiring treatment with occipitocervical fixation. In this paper the authors present their technique of craniocervical fixation achieved with the cephalad extension of posterior C1-3 polyaxial screw and rods to polyaxial screws placed in the occipital condyles. They retrospectively analyzed occipital condyle morphology obtained from CT analyses of 40 patients with normal cervical spines, evaluated occipital condyle screw placement feasibility in 4 cadav… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 55 publications
1
33
4
Order By: Relevance
“…Other anatomical structures possibly affected by the C0-C1 transarticular screw are the C2 root and surrounding venous plexus. 5,21,23) If the C2 root hinders screw positioning or visualization of the screw entry point, the C2 root can be resected to achieve reasonable space and angle for screw placement. The incidence of neuropathic pain from C2 root sacrifice is very low.…”
Section: Discussionmentioning
confidence: 99%
“…Other anatomical structures possibly affected by the C0-C1 transarticular screw are the C2 root and surrounding venous plexus. 5,21,23) If the C2 root hinders screw positioning or visualization of the screw entry point, the C2 root can be resected to achieve reasonable space and angle for screw placement. The incidence of neuropathic pain from C2 root sacrifice is very low.…”
Section: Discussionmentioning
confidence: 99%
“…6 Occipitocervical fixation from C0-C2 (n = 3) and C0-T2 (n = 1) was performed with the goal of decompression and stabilization of this region. All patients had preoperative neurological dysfunction.…”
Section: Study Samplementioning
confidence: 99%
“…Adult cadaveric studies have demonstrated the occipital condyles (C-0) to be a feasible fixation point. 4,6,13,14,21,[30][31][32] Subsequently, successful demonstration of this technique has been reported in adults 6,30 and in 1 pediatric patient. 4 In this paper, we present a series of 4 pediatric patients using our described technique.…”
mentioning
confidence: 99%
“…Real-time CT-based intraoperative neuronavigation can diminish the possibility of such inaccuracies. 13 Iso-C3D navigation has been well described for use in cervical spine surgery. 13,16,24 Hott et al demonstrated the intraoperative use of the Iso-C3D C-arm in a series of 30 patients with varied pathology of the cervical spine, including traumatic, degenerative, congenital, and neoplastic conditions.…”
Section: Discussionmentioning
confidence: 99%